2010
DOI: 10.1007/s11661-010-0436-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Failures during Cyclic Oxidation of Yttria-Stabilized (7 to 8 Weight Percent) Zirconia Thermal Barrier Coatings Fabricated via Electron Beam Physical Vapor Deposition and Air Plasma Spray

Abstract: The failures during oxidation of electron beam physical vapor deposition (EBPVD) and air plasma spray (APS) yttria-stabilized zirconia (YSZ) thermal barrier coatings (TBCs) on different bond coats, namely, platinum-modified aluminide and NiCoCrAlY, are described. It is shown that oxidation of the bond coats, along with defects existing near the TBC/bond coat interface, plays a very important role in TBC failures. Procedures to improve TBC performance via modifying the oxidation characteristics of the bond coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Similarly Zhu et al report thin dense lamellar YSZ coatings [14]. Many other authors have reported examples of PS-PVD coatings [1,6,7,[9][10][11][12][13][15][16][17].…”
Section: Coating Examples (Ps-pvd and Ps-tf)mentioning
confidence: 98%
“…Similarly Zhu et al report thin dense lamellar YSZ coatings [14]. Many other authors have reported examples of PS-PVD coatings [1,6,7,[9][10][11][12][13][15][16][17].…”
Section: Coating Examples (Ps-pvd and Ps-tf)mentioning
confidence: 98%
“…The most important elements that cause the formation of these cracks on TBC and TGO layer are stresses that occur as a result of TGO growth, phase transformations in bond coat, changes in bond coat during thermal cycle and sintering of TBC. Once the cracks form, they propagate and coalesce and result in failure of the coating [83][84][85].…”
Section: Thermal Shock Conceptmentioning
confidence: 99%
“…The rate of mismatch between superalloy substrate material and top coat affects elastic strain energy that is stored during cooling from working temperature. High amount of strain energy causes early removal/breaking of coating as a result of cycling [84,[87][88].…”
Section: Thermal Shock Conceptmentioning
confidence: 99%
“…If crack growth increases, the value of the elastic modulus will change and that will hamper the TBC life period under service conditions [13][14][15]. The failure of the coatings depends on cracks, show when they propagate and result in failure [16][17][18].…”
Section: Introductionmentioning
confidence: 99%